2022
DOI: 10.1021/acs.jpcc.2c04813
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Phase Equilibrium and Kinetics of Electrochemically Driven Phase Transition in CoOxHy during Electrocatalytic Reactions

Abstract: Water splitting is one of the most promising methods for mass production of green hydrogen (H2), with the oxygen evolution reaction (OER) being the current main kinetic bottleneck. Cobalt (oxy-)­hydroxides are among the most active electrocatalysts for OER in alkaline electrolytes free from rare-earth metals. However, identifying the active phase of electrocatalysts under operational OER conditions is often difficult, which largely impedes the design of cobalt-based electrocatalysts with improved performance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…[35d,69] For example, by using UV-vis spectroelectrochemistry, Baeumer et al found that a NiOOH-like surface monolayer forms on Ni-terminated LNO surfaces, but it is not observed on La-terminated films. [35d] Therefore, advanced in situ/operando electrochemical characterization tools, such as Raman spectroscopy, [70] XAS, [71] AFM, [72] and TEM, [73] need to be performed in the near future to generate insight into the dynamic surface changes of RNO electrocatalysts at the atomic scale and establish new principles for the effective design and use of these materials.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…[35d,69] For example, by using UV-vis spectroelectrochemistry, Baeumer et al found that a NiOOH-like surface monolayer forms on Ni-terminated LNO surfaces, but it is not observed on La-terminated films. [35d] Therefore, advanced in situ/operando electrochemical characterization tools, such as Raman spectroscopy, [70] XAS, [71] AFM, [72] and TEM, [73] need to be performed in the near future to generate insight into the dynamic surface changes of RNO electrocatalysts at the atomic scale and establish new principles for the effective design and use of these materials.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…Halogen bonding interaction involving CO 2 has been investigated by several groups 31–34 . Yang et al 35 reported that C and O atoms of CO 2 simultaneously interact with XY (X = Cl, Br and Y = F, Cl, and Br) by forming ring‐shaped CO 2 ∙X(Y)∙CO 2 complexes.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the binding distances and interaction strengths are closely associated with the electronegativity of X and Y atoms and that the optimized geometries and the stretching vibrational frequencies of these complexes are different from the individual (CO 2 ) 2 , CO 2 ∙∙∙XY and YX∙∙∙CO 2 dimer. Zhu et al evaluated the Br···O halogen‐bonding interactions between CO 2 and brominated ion pairs; 32 the results show that the Br∙∙∙O interactions are basically electrostatic in nature and belong to conventional weak halogen bonds. Moreover, the complexes formed between C and O atom of CO and dihalogen molecule (e.g., FCl···CO, Cl 2 ···CO, Br 2 ···CO, BrCl···CO, ClBr···CO, ICl···CO, ClI···CO, IBr···CO, BrI···CO, Cl2···OC, Br 2 ···OC, BrCl···OC, ClBr···OC, ICl···OC, and ClI···OC) have been extensively reported in the previous studies 36–39 .…”
Section: Introductionmentioning
confidence: 99%